Deforestation perspectives of dry temperate forests: main drivers and possible strategies - Ali, Ehsan; Azhar, Muhammad Farooq; Alam, Edris; Rehman, Zainab; Ullah, Sami; Ahmad, Aqeel; Towfiqul Islam, Abu Reza Md.; Zaman, Wajid; Javed, Muhammad; Mittal, Praveen (Frontiers in Environmental Science, 2023)
Deforestation is the accelerating factor of climate change in developing countries. The German Watch Report 2020 had rated Pakistan number 7th most affected country due to adverse impacts of climate change. The problem of deforestation poses an existential danger to the forest-depleted country. It is of utmost importance to predict the main drivers to control deforestation. This study was conducted from October 2021 to August 2022 in dry temperate forests of the Chilas to investigate the current condition, causes of deforestation, and predicted the main drivers by using a binary regression model. Stratified random sampling techniques and fixed area plot method were used and taken ground measurements during field inventory to access current situation of deforestation. While a non-probability quota sampling technique and semi-structured questionnaire were utilized A semi-structured questionnaire was utilized for the determination of main drivers of deforestation through respondent's survey. The forest inventory result showed that most trees fall in immature and sub-mature (mainly in 10-20 and 20-30 cm) diameter classes while the binary logistic regression model predicted dominating four primary drivers (unsustainable fuel wood extraction, unsustainable timber extraction and & urban crawling and rural expansion/habituation, and free and uncontrolled livestock grazing) and one secondary driver (wood for energy needs). To address the underlying causes of deforestation, the government must supply alternate energy sources, as well as other economic possibilities to reduce dependency on forests.